2005
DOI: 10.1530/eje.1.02030
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of pituitary tumours in the elderly: a review based on personal experience and evidence of literature

Abstract: An increasing proportion of pituitary adenomas are recognized in the elderly, raising the question of their optimal diagnosis and management. Age-related endocrine changes and associated diseases may significantly modify the clinical presentation and hormonal evaluation of these patients. About 80% of pituitary adenomas in this age group are non-secreting, requiring careful differential diagnosis with non-adenomatous sellar lesions. In this group, visual deterioration and hypopituitarism remain the leading sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 92 publications
7
39
2
3
Order By: Relevance
“…It has been reported that 80% of pituitary tumors in the elderly over 65 years of age are non-secreting 21 . In this sample, most of the patients were over 40 years of age (61.7%).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that 80% of pituitary tumors in the elderly over 65 years of age are non-secreting 21 . In this sample, most of the patients were over 40 years of age (61.7%).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that T 4 dosage based on bw and aiming at fT4 in the upper reference range is superior to titration of T 4 T REATMENT OF hypopituitarism has improved over the last two decades, due to refined laboratory tests and availability of more physiological replacement regimens (1,2). However, it is a well-known clinical notion that quality of life remains impaired despite substitution therapy, including T 4 , hydrocortisone, sex hormones, and GH.…”
Section: Discussionmentioning
confidence: 99%
“…Most pituitary tumours in this age group are large, slowly growing invasive tumours (179,180). Low growth rate of tumour remnants is reported by some (in 21% of the patients despite subtotal and partial tumour resections), while other authors report progression rates comparable in elderly and young patients (178,179,180). There is no absolute contraindication to either radiotherapy or oncological drugs in the elderly.…”
Section: Special Circumstances a Paediatricmentioning
confidence: 92%
“…Elderly Pituitary tumours in the elderly (patients older than 65 (176) are mostly clinically non-functioning (NFPA), although in general, they stain positive for gonadotroph hormones (177,178). Most pituitary tumours in this age group are large, slowly growing invasive tumours (179,180). Low growth rate of tumour remnants is reported by some (in 21% of the patients despite subtotal and partial tumour resections), while other authors report progression rates comparable in elderly and young patients (178,179,180).…”
Section: Special Circumstances a Paediatricmentioning
confidence: 99%